A critical and comprehensive review of the removal of thorium ions from wastewater: Advances and future perspectives - Senol, Zeynep Mine; El Messaoudi, Noureddine; Miyah, Youssef; Georgin, Jordana; Franco, Dison Stracke Pfingsten; Kazan-Kaya, Emine Sena; Cigeroglu, Zeynep (Elsevier, 2025)
This review article critically evaluates recent developments in removing thorium (Th) ions from wastewater and discusses future perspectives. Moreover, it is imperative to develop effective and sustainable techniques for removing Th due to the significant environmental and health risks its contamination produces. This review is done to understand the recent technologies and strategies developed for the removal of Th ions from wastewater and to evaluate their efficiency, feasibility, and environmental friendliness. Removal of Th ions from wastewater is an urgent issue due to the radiotoxicity and chemical toxicity of Th. This review may facilitate a broad understanding of the advances in various methods used for the removal of thorium ions through adsorption, ion exchange, membrane technologies, and bioremediation. Again, the article tries to spotlight the problems or gray areas associated with the different techniques developed so far, thereby suggesting scopes for future research and improvement. It is hoped that this review can successfully guide the development of new and more powerful approaches to mitigating Th contamination in wastewater by synthesizing leading-edge research findings and advances for better environmental protection and public health safety. It is of critical importance to protect the environment and human health from the toxic effects of radioactive thorium mixed into life-threatening wastewater. Because a clean environment means a more livable world left to future generations.
Keywords: Radioactivity; Thorium ion removal; Wastewater treatment; Advanced technologies; Environmental pollution; Environmental protection